Hyperleptinemia in Neonatally Overfed Female Rats Does Not Dysregulate Feeding Circuitry - Ziko, Ilvana; Sominsky, Luba; Nguyen, Thai-Xinh; Yam, Kit-Yi; De Luca, Simone; Korosi, Aniko; Spencer, Sarah J. (Frontiers in Endocrinology, 2017)
Neonatal overfeeding during the first weeks of life in male rats is associated with a disruption in the peripheral and central leptin systems. Neonatally overfed male rats have increased circulating leptin in the first two weeks of life, which corresponds to an increase in body weight compared to normally-fed counterparts. These effects are associated with a short-term disruption in the connectivity of neuropeptide Y (NPY), agouti-related peptide (AgRP) and pro-opiomelanocortin (POMC) neurons within the regions of the hypothalamus responsible for control of energy balance and food intake. Female rats that are overfed during the first weeks of their life experience similar changes in circulating leptin levels as well as in their body weight. However, it has not yet been studied whether these metabolic changes are associated with the same central effects as observed in males. Here we hypothesised that hyperleptinemia associated with neonatal overfeeding would lead to changes in central feeding circuitry in females as it does in males. We assessed hypothalamic NPY, AgRP and POMC gene expression and immunoreactivity at 7, 12, or 14 days of age, as well as neuronal activation in response to exogenous leptin in neonatally overfed and control female rats. Neonatally overfed female rats were hyperleptinemic and were heavier than controls. However, these metabolic changes were not mirrored centrally by changes in hypothalamic NPY, AGRP, and POMC fiber density. These findings are suggestive of sex differences in the effects of neonatal overfeeding and of differences in the ability of the female and male central systems to respond to changes in the early life nutritional environment.